Existence and regularity results for degenerate parabolic problems in the presence of strongly increasing regularizing lower-order terms and L^m-data/Dirac mass - Abdellaoui, Mohammed; Redwane, Hicham (Ukrains’kyi Matematychnyi Zhurnal, 2023)
UDC 517.9 We study the existence and regularity results for degenerate parabolic problems in the presence of strongly increasing regularizing lower-order terms and L^m-data/Dirac mass.